Mediación pedagógica en entornos virtuales para el logro de resultados de aprendizaje en la asignatura de Fisiología Humana y Comparada (Repertorio Científico, 2024)
The subject of Human and Comparative Physiology belongs to the Natural Sciences Teaching program of the State Distance University. According to its curricular description, it is offered under the virtual modality, using different virtual environments where the information, content and mediation activities necessary to achieve the learning results are developed. Pedagogical mediation focuses on the fulfillment of learning outcomes and guaranteeing the inclusion of the transversal axes in formative and summative activities of the course. The objective of the article is to determine the achievement obtained by students with respect to the learning results established in the curricular design, based on the mediation carried out in virtual environments. For this purpose, the teaching strategies implemented in the second quarter of 2022 were analyzed qualitatively and the level of achievement in the evaluation instruments presented by the 52 enrolled students along with the pedagogical strategies implemented was quantitatively analyzed. The results obtained demonstrate that an active, collaborative and formative evaluation is necessary to achieve the development of learning results. It is concluded that pedagogical mediation in virtual environments must be planned, using evaluation instruments appropriate to the needs, enhancing formative evaluation, with the support of the teacher as a facilitator for the achievement of learning results by the student body
Keywords: virtual environment, learning outcomes, human and comparative physiology, pedagogical mediation, learning instruments